2017
DOI: 10.1007/s10973-017-6204-9
|View full text |Cite
|
Sign up to set email alerts
|

Thermo-derivative analysis of Al–Si–Cu alloy used for surface treatment

Abstract: The only effective way to design, produce, analyse and optimise new and existing industrial thermal processes and also laser-based processes is to develop a quantitative knowledge and understanding of the dependence between temperature and time, which allow the desired forming of properties of the final products. The purpose of this paper was the performance of thermoderivative analysis using the UMSA platform of aluminium alloy cooled at chosen rate, for obtaining characteristics used later for laser treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…NETZCH Proteus-Thermal Analysis-version 5.2.1 software was used for processing the DTA-TG experiment. The DTA peaks were established on the heating curve along with the transformation enthalpy [28,29,[38][39][40].…”
Section: Equipmentmentioning
confidence: 99%
“…NETZCH Proteus-Thermal Analysis-version 5.2.1 software was used for processing the DTA-TG experiment. The DTA peaks were established on the heating curve along with the transformation enthalpy [28,29,[38][39][40].…”
Section: Equipmentmentioning
confidence: 99%
“…Similar precipitates were also reported by other studies for the same aluminum alloy. 2931 Additionally, it was reported that the hard and solid nano-particles served as the nuclei of β-Si phase and enhanced the resistance to the growth of α-Al phase during the solidification process of nano-composites. 9
Figure 2.OM images of various specimens including: (a) sample 750-0, (b) sample 750-2, (c) sample 750-4, (d) sample 800-0, (e) sample 800-2 and (f) sample 800-4.
…”
Section: Resultsmentioning
confidence: 99%
“…The determination of the laser treatment parameters is also important, particularly the laser power, to achieve a high value of layer hardness to protect the new developing material from losing its properties and to make the tool surface more resistant. Furthermore, EDS microanalysis was applied to determine the chemical composition of the created surface layer [15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%